A return to the land after tourism? Chinchero (Peru) in times of pandemic. (23rd May 2022) - García, Pablo
The Andean town of Chinchero, near Cuzco, has traditionally been an agricultural spot. However, over the last few decades agriculture has been in recess as the region experienced a surge in international tourism. Nowadays the covid-19 crisis is having a tremendous impact on the tourism business in Peru, as the country struggles to control the pandemic and the international borders have been closed since March. Considering the new scenario, this paper examines the consequences of the collapse of the tourism industry for the agricultural production in Chinchero. Specifically it asks whether or not people's perceptions and attitudes towards agriculture have substantially changed or not in the midst of the pandemic, and the extent to which these perceptions may somehow redress the town's increasing trend towards depeasantisation and touristification.